2011
DOI: 10.5194/acp-11-5289-2011
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of biomass burning in WRF-Chem: impact of wildfires on weather forecasts

Abstract: Abstract.A plume rise algorithm for wildfires was included in WRF-Chem, and applied to look at the impact of intense wildfires during the 2004 Alaska wildfire season on weather simulations using model resolutions of 10 km and 2 km. Biomass burning emissions were estimated using a biomass burning emissions model. In addition, a 1-D, timedependent cloud model was used online in WRF-Chem to estimate injection heights as well as the vertical distribution of the emission rates. It was shown that with the inclusion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
208
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 246 publications
(213 citation statements)
references
References 45 publications
(51 reference statements)
2
208
0
3
Order By: Relevance
“…Since it considers only a 10 day period, it is a case study that complements previous research that has examined longer periods (e.g., Freitas et al, 2007;Val Martin et al, 2010;Grell et al, 2011;Labonne et al, 2007). Two preprocessing methods for preparing biomass burning emissions are investigated, the standard WRF-Chem package (Prep chem sources) and the Naval Research Laboratory's (NRL) Fire Locating and Monitoring of Burning Emissions (FLAMBE).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since it considers only a 10 day period, it is a case study that complements previous research that has examined longer periods (e.g., Freitas et al, 2007;Val Martin et al, 2010;Grell et al, 2011;Labonne et al, 2007). Two preprocessing methods for preparing biomass burning emissions are investigated, the standard WRF-Chem package (Prep chem sources) and the Naval Research Laboratory's (NRL) Fire Locating and Monitoring of Burning Emissions (FLAMBE).…”
Section: Introductionmentioning
confidence: 95%
“…Klonecki et al (2003) showed that transport into the Arctic is consistent with isentropic flow, i.e., ascent along isentropic surfaces as a plume moves north. Grell et al (2011) included a plume rise algorithm for wildfires in WRF-Chem and examined the impact of intense wildfires during the 2004 Alaska wildfire season on weather simulations using model resolutions of 10 km and 2 km.…”
Section: Introductionmentioning
confidence: 99%
“…RADM2 in combination with the MADE aerosol module has already been widely used in literature (e.g. Grell et al, 2011;Minsenis and Zhang, 2010;Tuccella et al, 2012). Aqueous phase chemistry has been switched on as we expect this to be of relevance particularly when simulating aerosols during the wet season.…”
Section: Model Description and Setupmentioning
confidence: 99%
“…In case of biomass burning emissions the plumerise mechanism Grell et al, 2011) -already implemented in WRF-Chem was applied to determine the injection height of a biomass burning plume depending on heat fluxes, temperature, and wind speed. The contribution of different emission sources is separately determined using tagged tracers.…”
Section: Wrf-ghg Developmentmentioning
confidence: 99%